The potential of novel primers and universal adhesives to bond to zirconia - Amaral, Marina [UNESP]; Belli, Renan; Cesar, Paulo Francisco; Valandro, Luiz Felipe; Petschelt, Anselm; Lohbauer, Ulrich (Elsevier B.V., 2014)
Objectives: To investigate the adhesive potential of novel zirconia primers and universal adhesives to surface-treated zirconia substrates.Methods: Zirconia bars were manufactured (3.0 mm x 3.0 mm x 9.0 mm) and treated as follows: no treatment (C); air abrasion with 35 mu m alumina particles (S); air abrasion with 30 mu m silica particles using one of two systems (Rocatec or SilJet) and; glazing (G). Groups C and S were subsequentially treated with one of the following primers or adhesives: ZP (Z-Prime Plus), AZ (AZ Primer); MP (Monobond Plus); SU (ScotchBond Universal) and; EA (an Experimental Adhesive). Groups Rocatec and SilJet were silanized prior to cementation. Samples form group G were further etched and silanized. Bars were cemented (Multilink) onto bars of a silicate-based ceramic (3.0 mm x 3.0 mm x 9.0 mm) at 90 degrees angle, thermocycled (2.500 cycles, 5-55 degrees C, 30 s dwell time), and tested in tensile strength test. Failure analysis was performed on fractured specimens to measure the bonding area and crack origin.Results: Specimens from group C did not survive thermocycling, while CMP, CSU and CEA groups survived thermocycling but rendered low values of bond strength. All primers presented a better bond performance after air abrasion with Al2O3 particles. SilJet was similar to Rocatec, both presenting the best bond strength results, along with SMP, SSU and CEA. G promoted intermediate bond strength values. Failure mode was predominately adhesive on zirconia surface combined to cohesive of the luting agent.Conclusions: Universal adhesives (MP, SU, EA) may be a considerable alternative for bonding to zirconia, but air abrasion is still previously required. Air abrasion with silica particles followed by silane application also presented high bond strength values. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Zircona ceramics; Tensile bond strength; Primer; Air abrasion